Hydraulic Balance of a Eucalyptus urophylla Plantation in Response to Periodic Drought in Low Subtropical China - Zhang, Zhenzhen; Zhao, Ping; McCarthy, Heather R.; Ouyang, Lei; Niu, Junfeng; Zhu, Liwei; Ni, Guangyan; Huang, Yuqing (Frontiers in Plant Science, 2016)
As dominant cultivated plants in low subtropical China, Eucalypts is facing challenges due to climate changes. Experiments were conducted to determine the hydrologic balance of a Eucalyptus urophylla plantation in response to periodical drought. Trees displayed lower stomatal conductance (GS) and leaf water potentials (ΨL) in the dry season. The maximum reference GS at D=1 kPa (GSref-max) decreased by 22.4%, while specific hydraulic conductivity (ks) of trees of different sizes decreased by 45.3 - 65.6% from the wet to the dry season. Fairly stable leaf stomatal conductance (gs) with decreasing ΨL was also observed at ΨL <-1.6MPa, thus contributing to the high water-use efficiency (WUE) of this Eucalyptus specie. The lower stomatal sensitivity (-m = 0.53) in the dry season might be responsible for the high WUE, since we found an anisohydric behavior that was associated with photosynthetically active radiation (Q0). Larger trees were found to use water more efficiently than small trees, due to the higher sensitivity of ks to decreasing ΨL, which was also verified by the decreasing leaf carbon isotope discrimination (Δ13C) with increasing tree diameter. However, further studies are needed to verify the universality of these results for other Eucalyptus species in low subtropical China.